Peran Work Engagement Dalam Memediasi Pengaruh Career Adaptability dan Work Family Conflict Terhadap Job Performance Pegawai Pengadilan Tinggi Agama Semarang - Hilda Carolina; Suhana Suhana (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the mediating role of work engagement in the relationship between career adaptability and work family conflict on the job performance of employees at the Semarang Religious High Court. The study employs a quantitative approach using a census method involving 160 employees, consisting of High Court Judges and Civil Servants, with 122 valid questionnaires included in the analysis. Data were collected through structured questionnaires and analyzed using multiple linear regression and Sobel mediation tests with the assistance of SPSS. The results indicate that career adaptability does not have a significant effect on job performance, while work family conflict has a negative and significant effect on job performance. Furthermore, career adaptability has a positive and significant effect on work engagement, whereas work family conflict does not have a significant effect on work engagement. Work engagement is found to have a positive and significant effect on job performance. Mediation analysis reveals that work engagement mediates the effect of career adaptability on job performance. In addition, work engagement is also shown to mediate the effect of work family conflict on job performance. These findings highlight the importance of work engagement as a psychological mechanism in enhancing employee performance in the public sector.